Adaptive procedure of RS images classification with use of extended feature space - Markov N. G. Nikolai Grigorevich; Napryushkin A. A.; Zamyatin A. V. Aleksander Vladimirovich; Vertinskaya E. V. (2003, 2003)
The paper proposes an adaptive classification procedure (ACP) making the process of remotely sensed (RS) data classification more flexible and efficient in comparison with existing recognition methods. The ACP employs an improved scheme of forming feature space and adaptive decision rule allowing an optimal imagery classification method to be chosen during thematic processing. In the paper the basic principles of the ACP design and the results of classification method efficiency research are considered. Also the results of the ACP application for solving problems of landscape-ecological mapping of the Lake Chani area (Omsk region, Russia) and Pervomayskoe oil field (Tomsk region, Russia) using multispectral images from Russian satellite RESURS-01 are shown.